Being on the alert for continuously evolving influenza viruses: Early detection and rapid intervention of newly emerging viruses - (:unkn) unknown (My University, 2021)
Influenza viruses cause a major risk to human and animal health. Influenza virus capable of undergoing continuous evolution due to lack of proofreading mechanism during replication and high rate of mutation in their surface glycoproteins. Early detection and rapid intervention are crucial to mitigate the adverse outcomes of newly emerging influenza viruses. Evolution is a serious impediment to antiviral drugs and host immune system. The need for updating flu vaccines arising from perpetual evolution of influenza virus. Vaccines prepared for an earlier form of circulating influenza virus will not provide protection against newly emerging influenza viruses that is why flu vaccines need to be updated regularly. In addition, there is an urgent need for universal influenza vaccines which are capable of protecting against various strains of influenza virus. Hemagglutinin and neuraminidase are the key components of influenza virus which are more prone to mutation. Antigenic variation in influenza virus comes about because of genetic changes in their surface glycoproteins. These changes are known as “antigenic drift” and “antigenic shift”. This paper introduces the basics of influenza evolution, highlights the evolutionary history of influenza viruses and discusses how evolution impacts influenza intervention with particular emphasis on the current H5N1 Avian influenza epidemic. This paper also proposes the use of improved adjuvants in flu vaccines to trigger rapid and robust immune responses against newly emerging influenza viruses. Broad-spectrum immunologic adjuvant with ability to induce a wide range of immune responses can be used to develop an effective vaccines against newly emerging flu strains. Generally, this article illustrates how influenza virus undergoes evolution and presents ways of intervening continuously evolving influenza viruses.
Keywords: Antigenicdrift; Antigenicshift; Avianinfluenza; Earlydetection; Evolution; Flustrains; Hemagglutinin; H5N1; Influenza; Neuraminidase; Rapid intervention; Surface glycoproteins; Universal influenza vaccines